From Digital era to Digital Wellbeing era - Zangogianni Paraskevi-Chrysovalantou; Kavakli Evangelia (SHS Web of Conferences)
This study examines the concept of Digital Wellbeing (DWB), an emerging indicator of 21st-century quality of life. Using bibliometric analysis, 182 peer-reviewed articles from the Scopus database were analyzed to identify trends and patterns. Co-occurrence analysis of 689 keywords, visualized via VOSviewer, uncovered eight thematic clusters, including digital health, social media, digital addiction, privacy, and ethical design. The findings reveal a spectrum of perspectives, from optimistic views on technology’s ability to enhance human flourishing to critical approaches addressing its drawbacks. This study underscores the need for balanced, user-centered approaches to DWB, urging designers, policymakers, and researchers to prioritize ethical and sustainable practices. By mapping the intellectual structure of DWB, this research contributes to its conceptualization and provides a foundation for future empirical studies aimed at fostering a deeper understanding of the relationship between technology and human well-being.